Langerhans cell histiocytosis with extensive spinal and thyroid gland involvement presenting with quadriparesis: an unusual case in an adult patient - Sharifudin, Mohd Ariff; Johari, Joehaimey; Omar, Ahmad Sabri; Wan, Zulmi (Malaysian Orthopaedic Association (MOA), 2011)
Langerhans cell histiocytosis of the spine frequently presents as a solitary lesion and rarely results in neurological deficit. Involvement of thyroid tissue is also rare, even in multifocal disease presentations. We present an unusual variant of Langerhans cell histiocytosis in a 37-year-old man presenting with profound quadriparesis and incidental thyroid involvement. MR imaging and skeletal radiographs revealed widespread involvement of the spine. The patient underwent surgical resection of the tumour and stabilization of the spine. Diagnosis was confirmed by histological and immunohistochemistry analysis. Langerhans cell histiocytosis should be included in the differential diagnosis of radiolucent lesions of the spine in adults.